Program Psikoedukasi Terhadap Peningkatan Kualitas Hidup Pasien Gagal Ginjal Kronik - Pujiani Pujiani; Masruroh Masruroh (Jurnal EDUNursing, 2017)
Abstract Chronic renal failure or late stage renal disease (GGK) is a progressive and irreversible renal dysfunction in which the body's ability fails to maintain metabolism and fluid and electrolyte balance, which can lead to uremia (Smeltzer & Bare, 2002). One of the measures given to CKG patients is dialysis or hemodialysis. During hemodialysis therapy many of the problems experienced by patients, both biological and spiritual psychosocial problems such as worry about the condition of illness that can not be foreseen and disturbance in life. Patients also face financial problems, difficulty keeping jobs, disappearing sexual urges and impotence, depression resulting from chronic pain and fear of death. The condition of such CKG patients, desperately needs social support. The purpose of this study is to explore with FGD and develop psychoeducation programs to improve the quality of life of patients with CRF. The research type is descriptive. Research location in space hemodialisa RSUD Jombang. The sample of the study was GGK patients undergoing hemodialysis. The independent variable is the family psychoeducation program. The dependent variable is an improvement in the quality of life of patients with CRF. Research design with exploration of first and second FGD results with expert to prepare psychoeducation program including Preparing book (module) for patient and family Chronic renal failure, Conducting home visite, Forming peer group to strengthen support for patients with CRF.  Keywords: Family psychosis, quality of life, CRC